Trade-off between environment and economy: The relationship between carbon and inflation - Xu, Yingying; Li, Xiang; Yuan, Peng; Zhang, Yinpeng (Frontiers in Environmental Science, 2023)
The global pandemic since 2019 has caused crushing blow to healthy economic developments, particularly the harmonious development of environment and economy. Given the violent contradiction between health and economy, this study focuses on the controversial relationship between inflation and important environmental indicator. Specifically, we collect monthly data on inflation and carbon returns from three representative pilots in China and make a comprehensive investigation between carbon and inflation within the framework of the Environmental Kuznets Curve (EKC). Some significant empirical results are found. First, inflation shows a linear impact on carbon return, despite the signals of inflation vary in pilots. Second, there exists an inverted U-shape connection in Shenzhen and Guangdong pilots, which satisfies the assumption of EKC model. Third, inflation appears to be a non-negligible factor to the fluctuations in pilots, despite differences exist among pilots. Considering the pressing targets of carbon peak and carbon neutralization of China, this investigation provides important implications to policy makers in implementing differentiated policies in various regions, particularly in the turbulent situations caused by frequent climate policy changes and global pandemic developments.